1993
DOI: 10.1111/j.2042-3306.1993.tb02946.x
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of septicaemia in colostrum‐deprived foals

Abstract: Summary Fourteen mares and their foals were attended at parturition. After mare‐foal bonding, 8 colostrum‐deprived (CD) foals were removed from their dams, deprived of colostrum, and provided with an alternative milk source for the first 24 h of life. The mares were milked out every 2–4 h during this period to remove colostrum, after which the CD foals were returned to their mares and allowed to nurse. Six colostrum‐fed (CF) foals were allowed to suck colostrum in the normal manner. Foal serum IgG concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0
3

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(56 citation statements)
references
References 21 publications
2
51
0
3
Order By: Relevance
“…Another retrospective study indicated that 48% of foals with complete FTP had an infectious disease (septicaemia, arthritis, diarrhoea...) in the first weeks (Mc Guire et al, 1977). Other studies have produced similar conclusions (Chavatte and Collobert, 1994;Robinson et al, 1993).…”
Section: Passive Transfer Of Immunity In Horsessupporting
confidence: 71%
“…Another retrospective study indicated that 48% of foals with complete FTP had an infectious disease (septicaemia, arthritis, diarrhoea...) in the first weeks (Mc Guire et al, 1977). Other studies have produced similar conclusions (Chavatte and Collobert, 1994;Robinson et al, 1993).…”
Section: Passive Transfer Of Immunity In Horsessupporting
confidence: 71%
“…It has been suggested that FPT may be positively correlated with bacterial sepsis in foals [9,10,15,31,39,40]. These results indicate that early diagnosis and treatment of FPT are important.…”
Section: Discussionmentioning
confidence: 66%
“…Other studies have revealed a correlation between sepsis and the IgG concentration and survival in neonatal foals. 4,6,7 The survival data were not stratified by actual cause of death (euthanasia or natural death), thus it cannot be succinctly determined if failure of the passive transfer of IgG influenced the attending veterinarians' decision on recommendation for euthanasia.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] The strong association between increased risk for septicemia and mortality in foals with inadequate serum immunoglobulin G (IgG) concentrations has focused major emphasis on the role of IgG in preventing infection of neonates. 4,6,7 However, the fact that some foals with adequate transfer of colostral IgG succumb to infection and some foals with inadequate transfer of IgG do not acquire infection in the perinatal period 3 supports the premise that there are other significant components of transferred immunity that protect neonates against microbial disease. Indeed, evidence from other species suggests that additional factors in colostrum, such as lactoferrin, might also be important in innate immunity.…”
mentioning
confidence: 99%